Evidence for Functional Diversity between the Voltage-Gated Proton Channel Hv1 and Its Closest Related Protein HVRP1 - Kim, Iris H. (Public Library of Science, 2014)
The Hv1 channel and voltage-sensitive phosphatases share with voltage-gated sodium, potassium, and calcium channels the ability to detect changes in membrane potential through voltage-sensing domains (VSDs). However, they lack the pore domain typical of these other channels. Na(V), K(V), and Ca(V) proteins can be found in neurons and muscles, where they play important roles in electrical excitability. In contrast, VSD-containing proteins lacking a pore domain are found in non-excitable cells and are not involved in neuronal signaling. Here, we report the identification of HVRP1, a protein related to the Hv1 channel (from which the name Hv1 Related Protein 1 is derived), which we find to be expressed primarily in the central nervous system, and particularly in the cerebellum. Within the cerebellar tissue, HVRP1 is specifically expressed in granule neurons, as determined by in situ hybridization and immunohistochemistry. Analysis of subcellular distribution via electron microscopy and immunogold labeling reveals that the protein localizes on the post-synaptic side of contacts between glutamatergic mossy fibers and the granule cells. We also find that, despite the similarities in amino acid sequence and structural organization between Hv1 and HVRP1, the two proteins have distinct functional properties. The high conservation of HVRP1 in vertebrates and its cellular and subcellular localizations suggest an important function in the nervous system.